Fear in Uruguayan Literature: an Effect of Narrative Construction - Olivera, Jorge (Anales de Literatura Hispanoamericana, 2005)
The history of Uruguayan literature reveals two narrative tendencias: one of them realist, the other imaginative. Both tendencies can be traced from the nineteenth century to the present. This article focuses on the subject of fear in various short stories from the second narrative line, based on the imagination. The principal themes of this tendency are: estrangement, what is hidden and what is marginalised. Fear as a theme emerges principally within this imaginative tendency in fiction. It is usually related to the use of silence as a narrative strategy. What remains unsaid or hidden is the strategy used to generate fear in urban spaces or everyday actions. Within Uruguayan literature, this motive is not so much a strategy consciously used by the author as a product of the narrative events. It arises from the process of construction of the short stories and is linked to an interest in showing hidden zones of reality.
Keywords: Uruguayan literature; Fear; Narrative Silence